Amalan terbaik kepimpinan literasi pengetua dalam meningkatkan motivasi dan minat membaca pelajar menerusi Program Nilam : kajian kes di negeri Kedah - Zuridah Hanim, Md. Akhir (2018)
Ministry of Education Malaysia (MOE) introduced NILAM Programme in 1999 to encourage reading habits in school. Past research found that NILAM Programme not yet to achieve its objective, but there are excellent schools in NILAM activities that received recognition from MOE. Therefore, this study identifies the best practice of the principal as the literacy leader, internal and external factors which influenced the principal’s literacy leadership, and the role of the principal’s literacy leadership in increasing students’ motivation and reading interest through NILAM Programme. Research was conducted in three excellent schools in NILAM Programme. Qualitative data was collected via semi-structured interviews and document analysis. 22 respondents were involved, namely the principal, teachers, School Resource Coaches, Education Technology Officers and students. Document analysis were involved 55 school documents from 2005-2015. Data was thematically analysed through the content analysis method. Research findings showed that there are seven best practice of principal’s literacy leadership, namely the NILAM Programme leader, goal and direction setting, resource manager, change agents, encouraging the students, supporting the teachers and developing leadership. There are five internal factors that has influenced the principal’s literacy leadership, which are NILAM Programme committee, attitude, awareness and principals’ personal factors, strength of School Resource Centre, culture and reading interest, and students’ achievements. The five external factors are the role of government bodies, role of parents and Parent Teacher Association, private agencies, alumni and school recognition. Findings also showed that the principal focus on specific approaches to improving student’s motivation and reading interest. The research inputs produced the Secondary School Literacy Leadership Model as a guide to the principal. It is recommended that NILAM Programme be implemented in principal training, integrated in learning, and the principal’s role in the reading habits needs to be strengthened. Further research in various principal literacy leadership aspects has to be carried out to increase reading habits.